Anomalous Response in Heteroacene-Based Organic Field Effect Transistors under High Pressure - Ken-ichi Sakai (Electronics, 2014)
Carrier transport properties of organic field effect transistors in dinaphtho[2,3-b:2',3'-f]thieno[3,2-b]thiophene single crystals have been investigated under high pressure. In contrast to the typical pressure effect of monotonic increase in charge transfer rates according to the application of external hydrostatic pressure, it is clarified that the present organic semiconductor devices exhibit nonmonotonic pressure response, such as negative pressure effect. X-ray diffraction analysis under high pressure reveals that on-site molecular orientation and displacement in the heteroacene molecule is assumed to be the origin for the anomalous pressure effects.